Effectiveness, safety, and efficiency of a drive‐through care model as a response to the COVID‐19 testing demand in the United States. Issue 6 (20th December 2022) - Ravi, Shashank; Graber‐Naidich, Anna; Sebok‐Syer, Stefanie S.; Brown, Ian; Callagy, Patrice; Stuart, Karen; Ribeira, Ryan; Gharahbaghian, Laleh; Shen, Sam; Sundaram, Vandana; Yiadom, Maame Yaa A. B.
Abstract: Objectives: Here we report the clinical performance of COVID‐19 curbside screening with triage to a drive‐through care pathway versus main emergency department (ED) care for ambulatory COVID‐19 testing during a pandemic. Patients were evaluated from cars to prevent the demand for testing from spreading COVID‐19 within the hospital. Methods: We examined the effectiveness of curbside screening to identify patients who would be tested during evaluation, patient flow from screening to care team evaluation and testing, and safety of drive‐through care as 7‐day ED revisits and 14‐day hospital admissions. We also compared main ED efficiency versus drive‐through care using ED length of stay (EDLOS). Standardized mean differences (SMD) >0.20 identify statistical significance. Results: Of 5931 ED patients seen, 2788 (47.0%) were walk‐in patients. Of these patients, 1111 (39.8%) screened positive for potential COVID symptoms, of whom 708 (63.7%) were triaged to drive‐through care (with 96.3% tested), and 403 (36.3%) triaged to the main ED (with 90.5% tested). The 1677 (60.2%) patients who screened negative were seen in the main ED, with 440 (26.2%) tested. Curbside screening sensitivity and specificity for predicting who ultimately received testing were 70.3% and 94.5%. Compared to the main ED, drive‐through patients had fewer 7‐day ED revisits (3.8% vs 12.5%, SMD = 0.321), fewer 14‐day hospital readmissions (4.5% vs 15.6%, SMD = 0.37), and shorter EDLOS (0.56 vs 5.12 hours, SMD = 1.48). Conclusion: Curbside screening had high sensitivity, permitting early respiratory isolation precautions for most patients tested. Low ED revisit, hospital readmissions, and EDLOS suggest drive‐through care, with appropriate screening, is safe and efficient for future respiratory illness pandemics.